Performance of silicon solar cells under filtered spectra and different light intensities. (20th July 2017) - Thway, Maung; Sahraei, Nasim; Ren, Zekun; Chua, Soo Jin; Aberle, Armin G.; Buonassisi, Tonio; Peters, Ian Marius; Lin, Fen
Abstract: Solar cells operate under various light intensities. In addition, in a tandem solar cell configuration, the bottom cell receives a spectrum that is filtered by the top cell. The performance of the bottom cell at low light intensity is thus of great importance. In this paper, we study various types of silicon solar cells under various light intensities and filtered spectra. We find that, as expected, the short-circuit current varies linearly with the illumination intensity, regardless of the input spectrum. However, we also observe that for a constant number of incident photons but different long-pass filters (i.e., different photogeneration profiles), the short-circuit current density of the solar cells reduces with increasing cut-on wavelength of the used filter. According to our analysis, the loss in short-circuit current can be partly explained by the strong wavelength dependence of the external quantum efficiency at long wavelengths (1050–1200 nm) as well as the different carrier generation profiles under filtered spectra.